Biologic Therapies for Moderate to Severe Asthma in the Pediatric Population: A Practice Update - Concettina Tolomeo DNP, MBA, APRN, FNP- (SAGE Publishing, 2023)
Introduction Asthma is a common childhood condition. Up until recent years, the mainstay of long-term control treatment has been inhaled corticosteroids. While inhaled corticosteroids are very effective for most children with asthma, with the introduction of biologic therapies, additional options now exist for children with uncontrolled moderate to severe asthma. Purpose The purpose of this Practice Update is to provide nursing professionals with a summary of the biologic therapies currently available for the pediatric population and, to describe when they are indicated for inclusion in the plan of care for children with moderate to severe asthma. Conclusion By properly diagnosing asthma, and, selecting and administering appropriate asthma therapies, nursing professionals can help children with moderate to severe asthma lead healthy and active lives.